Crystal structure of ethane-1,2-diylbis(diphenylphosphine oxide) – dihydrogenperoxide (1/2), C26H28O6P2 - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C26H28O6P2, monoclinic, C2/c (no. 15), a = 12.8582(1) Å, b = 12.4664(1) Å, c = 15.4358(1) Å, β = 95.738(1)°, V = 2461.89(3) Å3, Z = 4, Rgt(F) = 0.0296, wRref(F2) = 0.0809, T = 100(2) K.